Fabrication of docetaxel-loaded hyaluronic acid coated zeolitic imidazolate framework‑8 as an effective treatment for leukaemia cancer cells and its apoptosis induction - Shuyi Wu; Henghua Li; Di Su; Na Lu (Journal of Experimental Nanoscience)
Drug delivery systems (DDSs) have been developed to carry an appropriate payload into the tumour’s area, accomplishing the goals of minimising potential bodily harm and enhancing therapeutic efficacy. Here, we fabricated a one-pot method for encasing docetaxel (DTX) in zeolitic imidazolate framework-8 (ZIF-8) composites called DTX@ZIF-8. The DTX@ZIF-8/HA nanoplatform is then formed by coating the DTX@HA with a hyaluronic acid (HA). Notably, the loading rate increased to 43.0% at a DTX dose of 1 mg/mL. The findings confirmed that HA could prolong blood flow and improve the tumour-specific formation of DDS. It may also be an innovative ‘switch’ and tumour-targeted ‘guider’. Hyaluronidase (HAase) in the tumour microenvironment (TME) may break down the HA shell, exposing the wrapped DTX@ZIF-8 and causing ZIF-8 to break down in the acidic tumour microenvironment, releasing the loaded DTX. The apoptosis mechanism was investigated using various biochemical staining and flow cytometric analysis. As a result, the DTX@ZIF-8/HA nanoplatforms were developed as an on-demand, tumour-specific drug delivery system, increasing the effectiveness of treatment.